2017
DOI: 10.5812/hepatmon.44695
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hepatitis A Virus Infection Prevalence Among Eastern Mediterranean and Middle Eastern Countries: A Systematic Review and Pooled Analysis

Abstract: Context: Hepatitis A virus (HAV) infection is the most common type of acute viral hepatitis that has been proposed as an important public health issue. Most of the countries in WHO Eastern Mediterranean region (EMR) and Middle East (ME) have a high endemicity of HAV infection. To provide a comprehensive estimation of the epidemiology of HAV in this region, we carried out a systematic review on the literature reporting the prevalence of HAV infection in the EMR and ME.Evidence Acquisition: We conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…These waters are the main source of agriculture irrigation and if contaminated they are also a source of infection for the human population. Consistent with previous reports [5], our results show that the prevalence of HAV Ab increases with age, suggesting the cumulative exposure to HAV with time. In other countries of the Eastern Mediterranean Region, high seroprevalence of HAV has been previously reported.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These waters are the main source of agriculture irrigation and if contaminated they are also a source of infection for the human population. Consistent with previous reports [5], our results show that the prevalence of HAV Ab increases with age, suggesting the cumulative exposure to HAV with time. In other countries of the Eastern Mediterranean Region, high seroprevalence of HAV has been previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…In Afghanistan (99%) [20], Iraq (96%) [21] and Palestine (93.7%) [22], with the lowest prevalence recorded in UAE and Kuwait with estimated prevalence rate below 50%. The overall HAV seroprevalence in Iran was estimated to be 62% and can be categorized as intermediate-endemicity for HAV infection [5].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the reduced level of immunity against HAV as well as several major risk factors for HAV infection (e.g., neighboring Afghanistan and health hazard of hepatitis A for Iranian pilgrims to Karbala-based shrines in Iraq) make anti-HAV vaccination an essential priority (25,30). In a landmark study by Safiabadi et al, data indicated that the prevalence of hepatitis A virus antibody (IgG) seroprevalence among Afghan and Iraqi populations are more than 95% (31). The best measures to prevent the disease are to vaccinate and to enhance awareness of the transmission and prevention methods.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis A rates increased significantly over the 13 years, with an annual percentage change of 15.3%. Hepatitis A is endemic in Middle Eastern countries, and Iraq has a higher prevalence than Somalia and Palestine, but lower than Afghanistan (Safiabadi et al, 2017). The increased incidence of hepatitis A could be attributable to poor primary hygiene practices, interrupted water supplies, and population displacement, all common in conflict settings (Turky et al, 2011).…”
Section: Other Who Surveillance Diseasesmentioning
confidence: 99%